Identification of co-regulated genes associated with doxorubicin resistance in the MCF-7/ADR cancer cell line - Miri, Ali; Gharechahi, Javad; Samiei Mosleh, Iman; Sharifi, Kazem; Jajarmi, Vahid (Frontiers in Oncology, 2023)
The molecular mechanism of chemotherapy resistance in breast cancer is not well understood. The identification of genes associated with chemoresistance is critical for a better understanding of the molecular processes driving resistance. This study used a co-expression network analysis of Adriamycin (or doxorubicin, DOX)-resistant MCF-7 (MCF-7/ADR) and its parent MCF-7 cell lines to explore the mechanisms of drug resistance in breast cancer. Genes associated with DOX resistance were extracted from two microarray datasets (GSE24460 and GSE76540) obtained from the Gene Expression Omnibus (GEO) database using the GEO2R web tool. The candidate differentially expressed genes (DEGs) with the highest degree and/or betweenness in the co-expression network were selected for further analysis. The expression of major DEGs was validated experimentally using qRT–PCR. We identified twelve DEGs in MCF-7/ADR compared with its parent MCF-7 cell line, including 10 upregulated and 2 downregulated DEGs. Functional enrichment suggests a key role for RNA binding by IGF2BPs and epithelial-to-mesenchymal transition pathways in drug resistance in breast cancer. Our findings suggested that MMP1, VIM, CNN3, LDHB, NEFH, PLS3, AKAP12, TCEAL2, and ABCB1 genes play an important role in DOX resistance and could be targeted for developing novel therapies by chemical synthesis approaches.